KEDUDUKAN HUKUM ANAK DI LUAR KAWIN SEBAGAI AHLI WARIS BERDASARKAN HUKUM ADAT DI DESA BAWOLAHUSA - Faana, Pikiran (JURNAL PANAH KEADILAN, 2024)
Every family always dreams that the family will always live happily, peacefully and prosperously because that is the direction of marriage, namely forming a happy, eternal and prosperous family. When a married couple in a marriage has children, they can form their own family. This research aims to find out the legal position of illegitimate children as heirs based on customary law in Bawolahusa Village. The type of research used is sociological legal research. Sociological legal research is legal research in the form of empirical studies to find the application and truth of law in society regarding something that happens. The type of approach used is descriptive using initial data as a comparison. Data collection techniques were carried out through interviews, observation and document study. The analysis of this research data is a descriptive research specification, which means research that aims to conduct research about something in the village and at a certain time. Based on research findings and discussions, the existence of the legal position of illegitimate children according to customary law in the village of Bawolahusa means that children who are illegitimate have no legal relationship with their biological father, unless the parents are united according to customary law, then the illegitimate child has the status Customary law in Bawolahusa Village. In customary law, an illegitimate child is understood as a child born outside a legal marriage and the child is only related to the mother. The existence of children outside of wedlock has its own legal consequences, which are viewed from customary law in positioning the position of children born outside of a legal marriage. So the position of an illegitimate child can only be recognized if the child has been recognized according to customary law.